Adhesion Protein Protocols - Coutts, Amanda S.; Coutts, Amanda S. (Methods in Molecular Biology,, 2013)
Cellular adhesion is a fundamental process that influences numerous biological activities such as morphogenesis, cell motility and division, as well as signalling. In addition, adhesion is a process important not only in normal physiology and development, but also in disease states such as tumourigenesis, cardiovascular disease, inflammation and infection. There are a plethora of proteins involved in adhesion-related events with a huge diversity in function. As a result, a wide variety of techniques exist to study adhesion related proteins and processes. In Adhesion Protein Protocols, Third Edition, chapters cover techniques to gain insight into the complex and incompletely understood processes that are involved in cellular adhesion. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Adhesion Protein Protocols, Third Edition will be useful for both those new to the field of adhesion protein research as well as the more experienced scientist.